Ultra-thin thermally grown silicon dioxide nanomembrane for waterproof perovskite solar cells - Cho, Myeongki; Jeon, Gyeong G.; Sang, Mingyu; Kim, Tae Soo; Suh, Jungmin; Shin, So Jeong; Choi, Min Jun; Kim, Hyun Woo; Kim, Kyubeen; Lee, Ju Young; Noh, Jeong Yeon; Kim, Jong H.; et al. (Journal of Power Sources, 2023)
Recently, perovskite solar cells (PSCs) have been attracting attention as the most promising alternative to conventional photovoltaics, mainly due to their high power conversion efficiency (PCE) of 25.7%. However, prior to commercialization, problems with their long-term stability caused by moisture should be solved. Accordingly, encapsulation is a crucial strategy for enhancing the long-term stability of PSCs, meaning a well-established strategy that includes an excellent barrier that protects them from the external environment while minimizing any damage during encapsulation is required. In this study, a room temperature thin-film encapsulation (RT-TFE) strategy is applied by transferring a defect-free thermally grown silicon dioxide nanomembrane (t-SiO2 NM), which is a well-known superior water molecule barrier, onto the PSCs. The average PCE of the devices decreased by only 0.012% with a standard deviation of 0.4249 during the entire encapsulation process, which was achieved by minimizing any thermal degradation of the photovoltaic components, including the perovskite and hole transport layers. This t-SiO2 NM successfully protected the PSC from external water molecules in an underwater condition for 31 days at room temperature, which is the longest reported survival time of encapsulated PSCs. As a result, the RT-TFE PSC maintained more than 98% of the initial efficiency.
Keywords: High power conversion; Long term stability; Nanomembranes; Photovoltaics; Power conversion efficiencies; Room temperature encapsulation; Thin film encapsulation; Ultra-thin; Water barriers; Water molecule; Long-term stability; Perovskite solar cells; Room temperature encapsulation; Thin-film encapsulation; Water barrier